Challenging gender roles in livestock research with radio messages - Mora Benard, María Alejandra (International Livestock Research Institute, 2016)
Interview with Alejandra Mora Benard (CIAT) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684